Realisation of customer focus from quality and forage safety aspects in the Hungarian mixed feed production - Csikai, Andrea (Acta Agraria Debreceniensis, 2014)
Customer focus is one of the main principles of Total Quality Management, and it is inevitable for long term, mutually successful vendorcustomer partnerships. The strictly controlled quality management systems of animal feed industry ensure that product quality meets the expectations of all parties involved and, indirectly the reliability of human food raw materials. Meanwhile, the participants of agricultural production are variably quality conscious, so feed manufacturers support their supply chain and also their customers with professional background and they play a key role in safe food chains from farm to fork.